2012
DOI: 10.1016/j.molbiopara.2011.10.011
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of VSG similarities in Trypanosoma brucei

Abstract: The protozoan parasite Trypanosoma brucei switches its variant surface glycoprotein (VSG) to subvert its mammalian hosts’ immune responses. The T. brucei genome contains as many as 1600 VSG genes (VSGs), but most are silent noncoding pseudogenes. Only one functional VSG, located in a telomere-linked expression site, is transcribed at a time. Silent VSGs are copied into a VSG expression site through gene conversion. Truncated gene conversion events can generate new mosaic VSGs with segments of sequence identity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 34 publications
1
34
0
Order By: Relevance
“…The invariant surface glycoproteins have been described more than 20 years ago [36] and although it was recently shown that a bloodstream stage-specific ISG75 family mediates suramin uptake [37], these invariant proteins remain poorly characterized and it is not known what role, if any, they play during the trypanosome development cycle. Atypical VSGs are another family of poorly characterized surface proteins and they were named atypical, because they lack cysteine residues in the C terminus [38]. Finally, the salivary gland CSP data set revealed four up-regulated transcripts encoding hypothetical proteins with predicted GPI anchors (Tb927.7.360, Tb927.7.380, Tb927.7.400, Tb927.7.420), that we previously showed by RT-PCR to be up-regulated in trypanosomes residing in salivary glands [16, 39].…”
Section: Resultsmentioning
confidence: 99%
“…The invariant surface glycoproteins have been described more than 20 years ago [36] and although it was recently shown that a bloodstream stage-specific ISG75 family mediates suramin uptake [37], these invariant proteins remain poorly characterized and it is not known what role, if any, they play during the trypanosome development cycle. Atypical VSGs are another family of poorly characterized surface proteins and they were named atypical, because they lack cysteine residues in the C terminus [38]. Finally, the salivary gland CSP data set revealed four up-regulated transcripts encoding hypothetical proteins with predicted GPI anchors (Tb927.7.360, Tb927.7.380, Tb927.7.400, Tb927.7.420), that we previously showed by RT-PCR to be up-regulated in trypanosomes residing in salivary glands [16, 39].…”
Section: Resultsmentioning
confidence: 99%
“…For gene families such as TcTS containing thousands of members, such methods are not possible. Alternatively, BLAST algorithms can be used to find local sequence matches between different family members [ 31 ] or phylogenetic incompatibility distribution can be used as an index to estimate recombination activity [ 13 ] and such methods have been applied to document recombination events in the T. brucei VSG gene family. However, such alternative methods, unlike the classical recombination analysis, cannot ensure both statistical support and the search-comprehensiveness of recombination events.…”
Section: Discussionmentioning
confidence: 99%
“…animation of the clustered BLAST analysis graph. 70 Using an even less stringent E-value of E < 1e-02, the separation between five N-terminal types is clearly observed. The video figure S1 published by Weirather et al 70 also illustrates additional features, such as the possibility of subgroups within the N1 cluster.…”
Section: Substructures Of Related Vsg N-terminal Types Can Also Be Obmentioning
confidence: 96%
“…These 3D visualizations reveal substructures not easily visualized in the 2D graphs. 70 2.2.10. Detection of mosaic genes BLAST hits between functional VSGs and other VSGs were used to illustrate regions of possible mosaic gene formation.…”
Section: D and 3d Visualizations Of Clustered Graphsmentioning
confidence: 99%
See 1 more Smart Citation